Brain temperature, body core temperature, and intracranial pressure in acute cerebral damage. Issue 4 (1st October 2001) - Rossi, S; Zanier, E Roncati; Mauri, I; Columbo, A; Stocchetti, N
Abstract : OBJECTIVES: To assess the frequency of hyperthermia in a population of acute neurosurgical patients; to assess the relation between brain temperature (ICT) and core temperature (Tc); to investigate the effect of changes in brain temperature on intracranial pressure (ICP). METHODS: The study involved 20 patients (10 severe head injury, eight subarachnoid haemorrhage, two neoplasms) with median Glasgow coma score (GCS) 6. ICP and ICT were monitored by an intraventricular catheter coupled with a thermistor. Internal Tc was measured in the pulmonary artery by a Swan-Ganz catheter. RESULTS: Mean ICT was 38.4 (SD 0.8) and mean Tc 38.1 (SD 0.8)°C; 73% of ICT and 57.5% of Tc measurements were ⩾38°C. The mean difference between ICT and Tc was 0.3 (SD 0.3)°C (range −0.7 to 2.3°C) (p=0. 0001). Only in 12% of patients was Tc higher than ICT. The main reason for the differences between ICT and Tc was body core temperature: the difference between ICT and Tc increased significantly with body core temperature and fell significantly when this was lowered. The mean gradient between ICT and Tc was 0.16 (SD 0.31)°C before febrile episodes (ICT being higher than Tc), and 0.41 (SD 0.38)°C at the febrile peak (p<0.05). When changes in temperature were considered, ICT had a profound influence on ICP. Increases in ICT were associated with a significant rise in ICP, from 14.9 (SD 7.9) to 22 (SD 10.4) mm Hg (p<0.05). As the fever ebbed there was a significant decrease in ICP, from 17.5 (SD 8.62) to 16 (SD 7.76) mm Hg (p=0.02). CONCLUSIONS: Fever is extremely frequent during acute cerebral damage and ICT is significantly higher than Tc. Moreover, Tc may underestimate ICT during the phases when temperature has the most impact on the intracranial system because of the close association between increases in ICT and ICP.